O-Linked β-N-Acetylglucosamine Modification: Linking Hypertension and the Immune System - dos Passos Junior, Rinaldo Rodrigues; Bomfim, Gisele Facholi; Giachini, Fernanda R.; Tostes, Rita C.; Lima, Victor Vitorino (Frontiers in Immunology, 2022)
The O-linked β-N-acetylglucosamine modification (O-GlcNAcylation) of proteins dynamically regulates protein function, localization, stability, and interactions. This post-translational modification is intimately linked to cardiovascular disease, including hypertension. An increasing number of studies suggest that components of innate and adaptive immunity, active players in the pathophysiology of hypertension, are targets for O-GlcNAcylation. In this review, we highlight the potential roles of O-GlcNAcylation in the immune system and discuss how those immune targets of O-GlcNAcylation may contribute to arterial hypertension.